Revitalizing Character Values in the Folklore of the Arjuna Mountain Slope Site - Sulistyo, Wahyu Djoko; Hafida, Mellina Nur; Maisaroh, Anisa Amalia (Diakronika, 2023)
Mount Arjuna is not only a popular tourist destination in Indonesia because of its outstanding natural beauty. Mount Arjuna also has a cultural heritage reflected in its sites. The slopes of Mount Arjuna have diverse folklore. Revitalization of folklore values on the slopes of Mount Arjuna is an essential step in maintaining cultural heritage and preserving local identity. The objectives of this study are 1) to study the folklore on the slopes of Mount Arjuna and 2) to design a revitalization of the folkloric values of the Lereng Gunung Arjuna site. This research uses a historical method consisting of four stages, namely heuristics, criticism, interpretation, and historiography, with an empirical approach. Data analysis was done comparatively by proving the Lereng Gunung Arjuna site and the Lereng Gunung Arjuna folklore. The results showed 1) there are 19 folklors contained in each site. Sites of Mount Arjuna Slope, namely Oento Boego Cave, Watu Kursi, Eyang Madrim, Rahtawu or Tampuono, Eyang Sekutrem, Eyang Abiyoso, Nogo Gini Cave, Sendang Dewi Kunti, Puthuk Lesung, Eyang Sakri, Eyang Semar, Dwarapala Statue, Makuthoromo, Sendang Widodari, Wejangan Cave, Rancang Kencono, Candi Wesi, Sendang Drajat, Sepilar; 2) Local wisdom as a concept of preserving the environment wrapped in harmony between the value of divinity-humanity-nature around. The existing local wisdom is used as an inspiration for the mechanism of social life. The implementation of revitalization requires support from the parties (multi-stakeholders), and then the folklore is preserved and adjusted by the social context and changing times. Various existing folklore has the potential to be transformed elsewhere. In education, it is introduced and converted to school students so that local wisdom as an ancestral heritage and potential can be changed as a guide for the next generation's life.